Thermal Performance of Analysis of Serpentine Channel Cold Plate for 18650 Cylindrical Lithium-Ion Battery - Fitri Wahyuni; James Julian; Rainer Samuel Fourlando; Riki Hendra Purba; Fathin Muhammad Mahdhudhu; Elvi Armadani; Nely Toding Bunga (Fakultas Teknik Universitas Pancasila, 2026)
This research evaluates the thermal performance of a liquid cooling system with serpentine channel inlets for an 18650 cylindrical lithium-ion battery module. The study analyzed an eight-cell module with a baseline configuration and variations featuring two, three, and four serpentine curves using computational fluid dynamics simulations validated against previous experiments. A fixed mass flow rate of 0.0001 kg/s was applied. Results showed all configurations-maintained battery temperatures below 37.5°C, preventing thermal runaway. The Baseline configuration achieved the lowest maximum temperature of 37.447°C and the highest performance factor (J/F factor) of 0.053. The two serpentine curves offered the best temperature uniformity (1.114°C) and highest heat transfer coefficient. Although more serpentine curves reduced maximum temperature, they increased pressure drop, decreasing the J/F factor. The study concludes that the serpentine cold plate design effectively manages thermal containment, with the two-curve configuration providing the best balance of heat transfer and temperature stability.